Germanium vertical Tunneling Field-Effect Transistor - Haehnel, D.; Oehme, Michael; Sarlija, M.; Karmous, A.; Schmid, M.; Werner, J.; Kirfel, O.; Fischer, I.; Schulze, J. (Solid-State Electronics, 2011)
The first realization of a pure Germanium bulk vertical Tunneling Field-Effect Transistor (vTFET) and a high Ion/Ioff ratio for a pure Silicon bulk vTFET are both reported. The manufacturing process, the electrical characteristics and key features and the differences of the two varieties of vTFET devices (pure Germanium bulk vTFET and pure Silicon bulk vTFET) will be discussed in detail. © 2011 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Germanium; Molecular beam epitaxy; Semiconductor processing; Silicon; Tunneling Field-Effect Transistor